Pharmacological mechanisms and potential clinical applications of Dihydromyricetin in neurological disorders - Zhang, Yike; Zhang, Tingting; Zhao, Manli; Li, Peichun; Liu, Tao; Xie, Jiangbo (Frontiers in Pharmacology, 2025)
Neurological disorders (e.g., Alzheimer’s disease, Parkinson’s disease, and stroke) have complex pathogenesis and affect a substantial proportion of the population; yet, available treatments have poor or limited efficacy, and the patients have a poor prognosis, with high morbidity and mortality. Dihydromyricetin (DHM), a flavonoid compound extracted from plants, has received widespread attention in recent years because of its diverse pharmacological effects. In vitro and in vivo studies have revealed its substantial antioxidant, anti-inflammatory, and neuroprotective properties, making it a promising candidate for the treatment of central nervous system disorders through multiple mechanisms and pleiotropic effects. Therefore, there is an urgent need to develop novel therapeutic strategies. DHM is an attractive candidate for the management of neurological disorders, but there is a lack of a systematic summary of the knowledge status and gaps. Therefore, to address this challenge, we systematically reviewed the pharmacological mechanisms of DHM in central nervous system disorders and its potential applications in related conditions. We analyzed the therapeutic potential and current challenges of DHM to provide a reference for its development and application as a novel therapeutic agent. The review suggests that DHM possesses significant potential for the management of neurological disorders.